Pengaruh Subsidi Listrik Terhadap Konsumsi Rumah Tangga Di Provinsi Sumatera Barat - Nurma Oktavia Sari; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2024)
Electricity subsidy is one of the poverty control programs that provides electricity subsidy assistance to poor and disadvantaged households paid by the Government of Indonesia to PT PLN. This study aims to determine and analyze the effect of electricity subsidies on household consumption in West Sumatra. The data is obtained from the National Socio-Economic Survey (SUSENAS) in 2022. The method used in this study is multiple linear regression analysis processed through the STATA 14 application. The results of the analysis show that electricity subsidies and location of residence have a negative and significant effect, while employment status and number of family members have a positive and significant effect on household consumption in West Sumatra in 2022. Policy recommendations from the research results to the government to pay more attention to rural households that lack electricity and the community to utilize electricity with a simple pattern, namely by saving electricity usage.